(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Enteric fever continues to remain a health problem as the causative organisms Salmonella has developed resistance to many of the antibiotics used. The aim of the present study was to evaluate frequency and antimicrobial susceptibility patterns with special reference to multidrug resistance (MDR) of Salmonella typhi and Salmonella paratyphi A, isolated from blood culture done in private hospitals, Dhaka, Bangladesh during November 2012 to January 2014. In total, 31 strains of S. typhi and 10 strains of S. paratyphi A, isolated and identified by standard microbiological procedures from 917 blood culture samples collected from suspected enteric fever cases, were tested for antimicrobial susceptibility by disc-diffusion method using 08 different antibiotics. All S. typhi and paratyphi A isolates were 90% sensitive to Ceftriaxone followed by Cefixime 84%. There were 35% S. typhi and 60% S. paratyphi A multidrug-resistant strains. Decreased susceptibility of S. typhi and S. paratyphi A was observed to Ciprofloxacin 48% and 80% respectively. All Salmonella isolates were resistant to Nalidixic acid (100%). This study concludes that precise information on antibiotic susceptibility pattern should be available to the clinician for optimal patients care. Ceftriaxone and Cefixime can be used as alternative anti-typhoidal treatment. Indiscriminate use of Ciprofloxacin should be strongly discouraged. Presence of MDR and quinolone resistance is concern and requires further study. J.Dhaka National Med. Coll. Hos. 2014;20(01): 3-8